المساهمة في دراسة تأثير حشرة المن على خصائص محصول الفلفل الحلو بمنطقة توقرت - بن طبة زوبيدة (University of Eloued جامعة الوادي, 2025)
This study aims to contribute to understanding the impact of infestation by the cotton aphid Aphis gossypii (Glover, 1877) on the morphological and physiological characteristics of sweet pepper (Capsicum annuum L.) crops in the Touggourt region. The study was conducted in a greenhouse and followed a field-based methodology that included a detailed description of the infested plants, along with an estimation of infestation levels in various plant parts.The findings showed that the aphid affects the growth and development of different plant organs to varying degrees. Visual examination revealed several characteristic symptoms of infestation, including leaf curling, yellowing, stunted new growth, delayed development or abortion of flowers, fruit deformation and reduction, as well as the presence of honeydew on the upper surfaces of leaves and fruits, which promoted the growth of sooty mold fungi. Microscopic analysis demonstrated that the morphological changes caused by the infestation were not only superficial, but also extended to the internal structures of plant tissues, thereby affecting the plant’s functional architecture. Despite the severity of the infestation, signs of partial resistance were observed, as some vital tissues remained relatively unaffected. Based on these results, the study provides recommendations for improving monitoring and control strategies, including support for biological control programs and the adoption of sustainable agricultural practices to mitigate the impact of this pest on sweet pepper production in greenhouses.
Keywords: Capsicum annuum L.; Aphis gossypii; Touggourt; Insect infestation; morphological changes .